Benign Enchondroma in a 40-Year-Old Female: Emphasizing the Importance of Early 18F-FES PET/CT Utilization - Tamer M. Dawud; Abdullah T. Dawud (Case Reports in Radiology)
A 40-year-old female with estrogen receptor–positive breast cancer underwent an initial staging using a technetium-99m methylene diphosphonate (Tc-99m MDP) bone scan, which revealed abnormal uptake in the femur without a patient history of prior trauma or associated symptoms. Subsequently, an MRI confirmed the presence of a well-defined lesion in the upper left femur. To rule out metastatic disease, an 18F-fluoroestradiol (FES) PET/CT was performed, demonstrating no ER expression. Following the PET/CT, a biopsy confirmed the presence of an enchondroma. This case underscores the importance of early utilization of 18F-FES PET/CT in breast cancer staging to minimize unnecessary additional procedures/imaging.